Community Service in the Field of Pharmacy through Aid Distribution and Health Education for Victims of the Aceh Tamiang Flash Flood: Kegiatan Pengabdian Masyarakat Bidang Farmasi melalui Penyaluran Bantuan dan Edukasi Kesehatan bagi Korban Banjir Bandang Aceh Tamiang - Ida Mukhlisa; Aida Apriani; Sasmiati Farach Dita; Siti Samaniyah; Yusrawati; Yunita Suffiana (Akademi Farmasi YPPM Mandiri, 2026)
The Community Service in the Field of Pharmacy through Aid Distribution and Health Education for Victims of the Aceh Tamiang Flash Flood was implemented as a form of social responsibility by pharmacy academics to support post-disaster community health recovery. This program aimed to provide basic medicines, conduct public health education, and raise awareness on rational drug use and hygiene practices. The activity was carried out on December 28, 2025, in Kedai Telaga Meuku Sa Village, Banda Mulia Subdistrict, Aceh Tamiang Regency, involving lecturers and students from the YPPM Mandiri Academy of Pharmacy, Banda Aceh. The implementation consisted of three stages, preparation, execution, and evaluation—using an experiential learning approach. The results indicated an increase in community knowledge regarding disease prevention and appropriate drug use (±84%), along with improved communication skills and social empathy among students. The activity also strengthened collaboration between academia, local government, and the community in enhancing community health resilience in disaster-prone areas. Nevertheless, the program had several limitations, including a relatively short implementation period and limited area coverage; therefore, a follow-up program is recommended through the establishment of community health cadres and sustainable mentoring activities.